Correction to: Recent advancement of fractional calculus and its applications in physical systems (The European Physical Journal Special Topics, (2023), 232, 14-15, (2347-2350), 10.1140/epjs/s11734-023-01002-4) - Boulaaras S.; Jan R.; Pham V.-T. (Springer Science and Business Media Deutschland GmbH, 2024)
In this article the keywords were missing. The following keywords are for the published original article https://doi.org/10.1140/epjs/s11734-023-01002-4: Bacterial infection Mathematical model Fractional-calculus, Endemic indicator CaputoFabriziooperator Dynamical behavior Ordinary differential equations Mathematical operators. The Author(s), under exclusive licence to EDP Sciences, Springer-Verlag GmbH Germany, part of Springer Nature 2023.